Predicting the development of rheumatoid arthritis in patients with early undifferentiated arthritis - E L Luchihina; D E Karateev; A A Novikov; E L Nasonov (Научно-практическая ревматология)
Diagnosis of rheumatoid arthritis (RA) at the beginning of the disease is a difficult task especially due to presence of a large group of pts with “undifferentiated arthritis” (UA) i.e. with inflammation of one or more joints which does not comply with a definite nosology. According to clinical experience UA is quite a serious condition which during a year transforms in definite RA in at least one third of pts. In 2007 Van der Helm-van Mil et al. proposed special criteria (“prediction rule”) allowing predicting transforming UA intoRA by counting prognostic index (PI). PI6 means low and PI8 - high probability of RA 37development during 1 year. Objective. To assess possibility of using prognostic criteria for determination of transforma- tion of UA into RA in Russian pts. Material and methods. 93 pts (84,9% - female) with early (disease duration no more than 12 months) UA were included. Mean age was 44,3±15,2 years, mean disease duration – 128,9±82,1 days (4,3±2,7 months). 59,1% of pts had olygoarthritis, 26,9% were rheumatoid factor seropositive, anti-cyclic citrullinated peptide antibodies (ACCP) were revealed in 29%. Examination with above mentioned methods to specify the diagnosis was performed trice during 12 months: at baseline, after 6 and 12 months. Results. During a year of follow up RA developed in 39(41,9%) pts. Mean value of PI was 5,18±2,48 (median 5,02 [3,01; 7,02]). PI values in pts with disease transformation into RA during a year were significantly higher (6,55±2,33) than in the rest of pts (4,18±2,1), p<0,0001. Analysis of discriminatory curve (ROC) was performed. Area under the curve statistics was 0,77 (SE 0,048, p=0,0001, 95% confidence intervals 0,68; 0,87). 64 (68,8%)pts had PI6, 17(18,3%) - PI≥8 and 12 (12,9%) – PI between 6 and 8. 17(26,6%) pts with PI≥6, 13 (76,5%) pts with PI≥8 and 9 (75%) pts with PI between 6 and 8 fulfilled criteria of RA in a year. Published data on European pts with UA cohorts analysis were compared with results of the present study. Conclusion. Using prognosis criteria for pts with UA in Russian pts gave satisfactory result. ROC analysis revealed PI level dividing transforming and not transforming into RA pts not around 8 as was demonstrated earlier but around 6. Differences between results of the present study and published data may be due to different factors including genetic features as well as clinical heterogeneity of pt groups from Western and Eastern Europe.